Instantaneously measured traits may detect non-plastic ecophysiological performances in response to drought, explaining distributions of Styrax species in the Cerrado - da Veiga, Eduardo B. [UNESP]; Habermann, Gustavo [UNESP] (Springer Nature, 2013)
We analyzed the differences between irrigated and non-irrigated plants of three congeneric Styrax species that present distinct distribution patterns in the physiognomies of the Cerrado vegetation in Brazil. Styrax ferrugineus showed a stomatal conductance (gs) unresponsive to soil water deficit in potted plants. This may explain the high gas exchange and photochemical efficiency found in this species, which is well adapted to the Cerrado sensu stricto (s. str.), a savanna-type vegetation. S. camporum, which is widely distributed in the Cerrado sensu lato (s. l.) areas, was the only species that exhibited increased intrinsic water use efficiency on the days of maximum water deficit. This result distinguishes S. camporum from S. pohlii, which is a forest species, since the gs of both species decreased during the days of maximum water stress. In contrast to other studies, we propose that instantaneously measured traits, such as leaf gas exchange rates and chlorophyll fluorescence, may be used to detect non-plastic performances in response to environmental stress, helping explain distinct geographical distributions of congeneric species in the Cerrado vegetation. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Brazilian savanna; Chlorophyll fluorescence; Leaf gas exchange; Leaf water potential; Semi-controlled conditions